Effects of planting date and variety on flooded rice production in the deepwater area of Thailand - Buddhaboon C. (2014)
Crop management plays an important role in the transition from a deepwater rice to a flooded rice production system but information about optimum management strategies are currently lacking. The goal of this study was to determine the effect of planting date and variety on flooded rice production in the deepwater area of Thailand. Two experiments were conducted at the Bang Taen His Majesty Private Development Project in 2009 and 2010 to represent conditions prior to flooding (early rainy season) and after flooding (dry season). The early rainy season crop covered the period from May to October 2009, while the dry season crop covered the period from November 2009 to April 2010. The experimental design was a split plot with four main plots and three sub plots replicated four times. The treatments for the main plot were various planting dates, while the treatments for the sub plots were rice varieties. The dates of the critical developmental phases of rice were recorded and biomass was sampled during the growing period. The collected data were statistically analyzed using ANOVA and treatment means were compared to identify the appropriate plating date and the best variety for the area. The highest average yield was obtained for variety PSL2 across transplanting dates from June 19 to July 23, with an average yield of 3898kgha-1. The dry season crop showed that both biomass and yield were affected by the interaction between planting date and variety. The highest yield was obtained for variety PTT1 transplanted on November 9. The research showed that the variety PSL2 is the most suitable variety for early rainy season production with a transplanting date ranging from June 19 to July 23, while the variety PTT1 planted on November 9 was the best management practice for the dry season crop. However, a high yielding flooded rice variety that has a short growth duration is still needed for this area. © 2011 Elsevier B.V.